Sustainable solutions for clean energy production - Batista, Virginia da Silva; Chagas, João Vítor da Silva; da Silva, Allem Karolyne Dino; da Silva, Yali Alves; Monteiro, Eliana Cristina Barreto; Campos-Takaki , Galba Maria (Seven Editora, 2023)
With the rampant increase of pollutants from various sources in recent decades, mainly fossil fuels, several negative consequences have been generated for the environment and human health. A sustainable alternative is to obtain energy through renewable sources such as biomass. of animal and/or vegetable origin used in the generation of energy and the manufacture of biofuels. The process of obtaining energy from biomass has two categories: traditional and modern. The main types of biofuels produced are biodiesel, biogas, bioethanol, biomethane, and vegetable oil. Biofuels can be grouped into first-generation, second-generation, third-generation, and fourth-generation. Because it is renewable, it is a potentially unlimited source, as well as less harmful to the environment, generating little pollution. The main advantages are low cost; easy storage; high energy efficiency; emission of fewer polluting gases; use of renewable resources. On the other hand, there is difficulty in the storage of solid biomass; collaborates for the formation of acid rain; high cost in the acquisition of industrial equipment; and deforestation at the production site. However, biomass is gaining traction worldwide as a sustainable alternative in clean energy production, as this is an important source of renewable energy. Countries such as the United States, China, India, and Germany are among those that use biomass to produce clean energy, mainly from agricultural and forestry waste. Brazil is one of the main producers of this type of energy in the world, due to its great potential for the production of renewable raw materials. Although it is a renewable and clean source, the implementation of projects for its use faces some challenges such as collection and transportation logistics, conversion technologies, financing, and regulation. DOI:https://doi.org/10.56238/alookdevelopv1-048